Misdiagnosis of Paget’s Disease of Bone in a Congenital Generalized Lipodystrophy Patient: Case Report - Freire, Erika Bastos Lima; Madeira, Mayara Ponte; Lima, Grayce Ellen da Cruz Paiva; Fernandes, Virginia Oliveira; Aguiar, Lindenberg Barbosa; Fontenele, João Paulo Uchoa; Montenegro, Ana Paula Dias Rangel; Marques, Thyciara Fontenele; Ozório, Renan Galvão; d’Alva, Catarina Brasil; Montenegro, Renan Magalhães (Frontiers in Endocrinology, 2021)
Paget’s Disease of Bone (PBD) is a common skeleton disorder in which diagnosis is suggested by radiological analyses. Congenital Generalized Lipodystrophy (CGL) is a rare, but an important radiologic differential diagnosis of Paget’s disease. Patients present total or almost total lack of subcutaneous adipose tissue, leptin deficiency and precocious ectopic lipid accumulation, which lead to intense insulin resistance, poorly controlled diabetes mellitus and hypertriglyceridemia. CGL subtype 1 and 2 present sclerosis and bone cysts that can be similar to pagetic lesions. The clinical correlation is, therefore, essential. We report a CGL patient with bone lesions in which the radiographic findings led to a misdiagnosis of PDB. This case report brings awareness to CGL, a life-threating condition. Its early recognition is essential to avoid clinical complications and premature death. Therefore, it’s important to consider CGL as PBD’s differential diagnosis, especially in countries with high prevalence such as Brazil.